Targeting the Non-catalytic RVxF Site of Protein Phosphatase-1 With Small Molecules for Ebola Virus Inhibition - Lin, Xionghao; Ammosova, Tatiana; Choy, Meng S.; Pietzsch, Colette A.; Ivanov, Andrey; Ahmad, Asrar; Saygideğer, Yasemin; Kumari, Namita; Kovalskyy, Dmytro; Üren, Aykut; Peti, Wolfgang; Bukreyev, Alexander; et al. (Frontiers in Microbiology, 2019)
Ebola virus (EBOV) is a non-segmented negative-sense RNA virus that causes a severe human disease. The ongoing EBOV outbreak in the Eastern part of Democratic Republic of the Congo has resulted to date in over 2000 confirmed cases including over 1000 deaths. Difficulties with vaccine administration indicate the necessity for development of new general drugs and therapeutic strategies against EBOV. Host Ser/Thr protein phosphatases, particularly PP1 and PP2A, facilitate Ebola virus (EBOV) transcription by dephosphorylating the EBOV VP30 protein and switching activity of the polymerase complex towards replication. Previously, we developed small molecule 1E7-03 that targeted host protein phosphatase-1 (PP1) and induces phosphorylation of EBOV VP30 protein thus shifting transcription–replication balance and inhibiting EBOV replication. Here, we developed a new EBOV inhibitor, 1E7-07, that potently inhibits EBOV replication and displays significantly improved metabolic stability when compared to previously described 1E7-03. Proteome analysis of VP30 shows that 1E7-07 increases its phosphorylation on Thr-119 and Ser-124 over 3-fold with p<0.001, which likely contributes to EBOV inhibition. We analyzed 1E7-07 binding to PP1 using a mass spectrometry-based protein painting approach. Combined with computational docking, protein painting shows that 1E7-07 binds to several PP1 sites including the RVxF site, C-terminal groove and NIPP1-helix binding pocket. Further analysis using surface plasmon resonance and a split NanoBiT system demonstrates that 1E7-07 binds primarily to the RVxF site. Together, detailed analysis of 1E7-07 binding to PP1 and identification of the RVxF site as the main binding site opens up an opportunity for future development of PP1-targeting EBOV inhibitors.